2021
DOI: 10.1111/gcb.15743
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on Asiatic black bear (Ursus thibetanus) and its autumn diet in the northern highlands of Pakistan

Abstract: Approximately 20%–30% of plant and animal species are at risk of extinction by the end of the 21st century owing to climate change. Range shifts and range contractions in plant species will dramatically affect the distribution of animals relying on them for food and shelter. The negative impacts of climate change on forested landscapes of the northern highlands of Pakistan (NHP) could change the species composition and distribution. The Asiatic black bear (Ursus thibetanus), a forest‐dwelling species, primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…Therefore, predicting the response from species to climate change, especially their potential habitats distribution, can be regarded as a great effort to help the planning and decision-making to improve the sustainability and adaptability of ecosystems [58]. Previous studies have shown that various plants and animal species can transfer suitable areas to high altitude and high latitude regions, so as to avoid the adverse effects of extreme weather and utilize available climate resources [59][60][61][62]. In order to formulate countermeasures to adapt to climate change, it is necessary to predict the impact of climate change on the potential distribution pattern of species [63].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, predicting the response from species to climate change, especially their potential habitats distribution, can be regarded as a great effort to help the planning and decision-making to improve the sustainability and adaptability of ecosystems [58]. Previous studies have shown that various plants and animal species can transfer suitable areas to high altitude and high latitude regions, so as to avoid the adverse effects of extreme weather and utilize available climate resources [59][60][61][62]. In order to formulate countermeasures to adapt to climate change, it is necessary to predict the impact of climate change on the potential distribution pattern of species [63].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported high intensities of human black bears con icts in Pakistan (Ali et al 2017; Kazmi et al 2019;Waseem et al 2020;Zahoor et al 2021c;Zahoor et al 2021d), however, there is no study available on activity pattern of black bears. In Taiwan, it was reported that in oak poor season, bears activity decreased and vice versa (Hwang and Garshelis 2007).…”
Section: Introductionmentioning
confidence: 98%
“…(ii) Maize crop is much nutritious, and milky in nature(Zahoor et al 2021c) and its ripening in September attracts black bears to reside at the fringes of forest, from where they could raid nearby maize crop elds easily. Beside Quercus spp Zahoor et al (2021d). reported the 2nd highest proportion of Zea mays in the scats of black bears during autumn in Machiara National Park.…”
mentioning
confidence: 94%
See 2 more Smart Citations